2016
DOI: 10.3177/jnsv.62.425
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Suppresses Macrophage Activation via Antioxidant Mechanisms in a CaPO<sub>4</sub>-Induced Mouse Model of Aneurysm

Abstract: SummaryAneurysm is characterized by balloon-like expansion of the arterial wall and eventual rupture of the aorta. The pathogenesis of aneurysm is associated with the degradation of matrix proteins by matrix metalloproteinases (MMPs) produced by activated macrophages. Although aneurysm is associated with significant mortality and morbidity, surgical intervention is the only proven treatment strategy. Therefore, development of therapeutic agents for aneurysm is greatly anticipated. Here, we demonstrated the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…FACS analysis with CaPO 4 -injured aortas showed that GSP administration signifi cantly decreased macrophage-derived CD54 expression (M1 marker) and increased macrophage-derived CD206 expression (M2 marker), which correspondingly plays a vasoprotective role via controlling the phenotype transformation of tissue-derived macrophages. Accumulating evidence (18) demonstrated that various natural products can decrease the expression of MCP-1 and IL-1β molecules, thus resulting in the inhibition of macrophage invasion into the vascular wall. In this way, the macrophage infi ltration and release of infl ammatory mediators triggered by vascular injury may be suppressed by GSP administration, which is more likely to enhance the protective mechanism underlying the suppression of vascular infl ammation and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…FACS analysis with CaPO 4 -injured aortas showed that GSP administration signifi cantly decreased macrophage-derived CD54 expression (M1 marker) and increased macrophage-derived CD206 expression (M2 marker), which correspondingly plays a vasoprotective role via controlling the phenotype transformation of tissue-derived macrophages. Accumulating evidence (18) demonstrated that various natural products can decrease the expression of MCP-1 and IL-1β molecules, thus resulting in the inhibition of macrophage invasion into the vascular wall. In this way, the macrophage infi ltration and release of infl ammatory mediators triggered by vascular injury may be suppressed by GSP administration, which is more likely to enhance the protective mechanism underlying the suppression of vascular infl ammation and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Puerarin at 2.5 mg/kg retarded CaPO4-induced aneurysm in mice. In vitro in TNF-α and CaPO4-stimulated macrophages, it reduced the Mmp9 mRNA expression, secreted protein production, as well as inhibited the production of ROS and the phosphorylation of inhibitor of NF-κB, ERK and p38 (Tanaka, Moriyama, Kawamura and Yamanouchi, 2016). In a mouse model of isoprenaline-caused myocardial fibrosis, puerarin at 600 and 1200 mg/kg restored myocardial fibrosis and attenuated the collagen volume fraction, collagen accumulation, hydroxyproline content in myocardial tissue and cardiac weight index.…”
Section: Othersmentioning
confidence: 95%
“…Puerarin at 2.5 mg/kg retarded CaPO 4 -induced aneurysm in mice. In vitro in TNF-α and CaPO 4 -stimulated macrophages, it reduced the Mmp9 mRNA expression, secreted protein production, as well as inhibited the production of ROS and the phosphorylation of inhibitor of I-κB, ERK and p38 ( Tanaka et al, 2016 ). Besides, it lessened SBP and heart rate, eased pain, reduced mRNA and protein expression of P2X 3 receptor (a member of P2X receptors family) in superior cervical ganglia, stellate ganglia and cervical dorsal root ganglia neurons, as well as down-regulated ATP-sensitive currents in superior cervical ganglia and cervical dorsal root ganglia neurons of myocardial ischemic rats ( Liu et al, 2014b ; Liu et al, 2014c ).…”
Section: Cadiovascular Effects Of Puerrarinmentioning
confidence: 99%